A molecular survey of hemoplasmas in domestic dogs from Turkey - Aktas, Munir; Ozubek, Sezayi (Elsevier Science Bv, 2018)
Mycoplasma haemocanis (Mhc) and Candidatus Mycoplasma haematoparvum (CMhp) are cell-wall-deficient bacterial pathogens that localize on the vertebrate erythrocyte surface. Prevalence of infection with these hemoplasmas and associated risks factors were ascertained from archived DNA samples collected from 621 domestic dogs (201 strays, 262 from shelters, 158 domestic pets) by species-specific PCR assay. The overall prevalence of infection was 15.3% (CI 12.5-18.4), with Mhc and CMhp single infection prevalence of 4.5% (CI 3.0-6.4) and 4.3% (CI 2.9-6.3), respectively. Dual infection with Mhc and CMhp was found in 6.4% (I 4.6-8.715). Infection rates for male (15.8%, CI 12.5-18.4) and female (14.5%, CI 10.5-19.4) dogs were not significantly different (P > 0.05), and the frequency of hemoplasmas was higher in adult dogs (18.9%, CI 15.1-23.2) than in young (9.5%, CI 6.1-14.0) (P < 0.05). Shelter and free-roaming stray dogs had higher prevalence of infection compared to domestic pet dogs (P < 0.05), but there was no significant difference in prevalence between free-roaming and shelter dogs (P > 0.05). A significant association between hemoplasma infection and the presence of Rhipicephalus sanguineus sensu lato was observed (P < 0.05). Presence of tick-borne pathogens (Babesia, Hepatozoon, Anaplasma, Ehrlichia) was also significantly associated with canine hemoplasmas (P < 0.05).
Keywords: Mycoplasma haemocanis; Candidatus Mycoplasma haematoparvum; Dog